KAJIAN ARSITEKTUR MELAYU PADA MASJID AL-OSMANI MEDAN: (STUDI KASUS : MASJID AL-OSMANI) - Endi Martha Mulia,; Sihotang, Harlen; Siagian, Mikhael G.D.; Tarigan, Eriyadi; Lee, Jason (Jurnal Sains dan Teknologi ISTP, 2025)
Al-Osmani Mosque in Medan, a legacy of the Deli Sultanate, is examined for its unique blend of Malay Deli architecture with Indian, Chinese, Spanish, and Middle Eastern influences. This study employs direct observation and comparative study with Azizi Mosque to analyze the application of Malay architectural elements within Al-Osmani. The main problem addressed is identifying which elements demonstrate the persistence of Malay features amidst prevailing foreign influences. The proposed solution is a detailed identification of distinctive colors, motifs, and ornaments typical of Malay architecture within the mosque. The findings indicate that despite cultural amalgamation, the dominance of golden yellow, floral and faunal motifs, and traditional ornamentation maintain the mosque’s strong Malay identity.